ANALISIS PENGARUH PENAMBAHAN PAC-R TERHADAP KARAKTERISTIK RHEOLOGY LUMPUR PEMBORAN YANG TERKONTAMINASI BATUBARA - Manik, Nijusiho; Rozi, Fathur; Painda, Esterina Natalia (PETROGAS: Journal of Energy and Technology, 2025)
ABSTRACTThe success of drilling activities is greatly influenced by drilling mud. Coal contamination in drilling mud will damage the mud’s performance in carrying out it function during drilling operations. Coal contamination in drilling mud can affect a number of physical properties of drilling mud such as density, rheology properties, and filtration loss. To maintain the performance of the drilling mud due to coal contamination in drilling activities, it is necessary to add Polyanionic Cellulose - Refined (PAC-R). Based on the reasearch results, the effect of coal contamination 1%, 2%, 3%, and 4% (sample B) can change the physical properties of drilling mud such as reducing the rheology value of drillinh mud and increasing the filtration loss value. Therefore, the addition of PAR-R additives is needed to control the physical properties of the drilling mud. From the results, the addition of PAC-R additives of 0,3% and 0,5% (samples C2 and C3) can provide changes to the rheology value of drilling mud according to the drilling mud specifications. This is because the PAC-R additive functions to reduce filtration in drilling mud and as a viscous in the mud to increase the rheology value of the mud.Keywords: Mud Drilling, Coal Contamination, Rheology Properties, PAC-R. ABSTRAKKeberhasilan kegiatan pemboran sangat dipengarui oleh lumpur pemboran. Kontaminasi batubara dalam lumpur pemboran akan merusak kinerja lumpur dalam menjalankan fungsinya selama operasi pengeboran. Kontaminasi batubara dalam lumpur pemboran dapat mempengaruhi sejumlah sifat fisik lumpur pemboran seperti densitas, sifat rheologi, dan filtration loss. Untuk menjaga kinerja lumpur pemboran tersebut akibat kontaminasi batubara dalam kegiatan pemboran, maka perlu penambahanan Polyanionic Cellulose - Refined (PAC-R). Berdasarkan hasil penelitian, pengaruh dari kontaminasi batubara 1%, 2%, 3%, dan 4% (sampel B) dapat merubah sifat fisik lumpur pemboran seperti menurunkan nilai rheology lumpur pemboran dan menaikan nilai filtration loss. Oleh karena itu dibutuhkan penambahan zat additive PAC-R untuk mengontrol sifat fisik lumpur pemboran tersebut. Dari hasil pengujian, penambahan zat additive PAC-R sebesar 0,3% dan 0,5% (sampel C2 dan C3) dapat memberikan perubahan terhadap nilai rheology lumpur pemboran sesuai dengan spesifikasi lumpur pemboran. Hal ini dikarenakan zat additive PAC-R berfungsi untuk mengurangi filtrasi dalam lumpur pemboran dan sebagai viscofier dalam lumpur untuk menjadi nilai rheologi lumpur.Kata kunci: Lumpur Pemboran, Kontaminas Batubara, Sifat Rheology, PAC-R.